PENGAJARAN BAHASA BERBASIS TUGAS (TASK BASED LANGUAGE TEACHING): PENDEKATAN YANG EFEKTIF DALAM PENGAJARAN BAHASA INGGRIS - Maria Cholifah (Fakultas Bahasa dan Sastra Universitas Kanjuruhan Malang, 2017)
This paper highlights the benefits of implementing Task-Based Language Teaching (TBLT) in teaching-learning of four skills of English. TBLT focuses on how English language is applied in accomplishing a certain task. TBLT also cultivates studenys’ self-efficacy and enthusiasm in learning. Task-based activities create advantageous atmospheres in language learning since they focus on the outcomes of learning by maximizing the use of Engliah language. Furthermore, this paper discusses the essence, the purposes, and the effects of TBLT in enhancing students’ four skills of English. Keywords: TBLT, four skills of English, teaching-learning of English.